Contactless calibration of microchanneled AFM cantilevers for fluidic force microscopy - Sebastian Sittl; Nicolas Helfricht; Georg Papastavrou (View, 2024)
Abstract Atomic force microscopy (AFM) is an analytical technique that is increasingly utilized to determine interaction forces on the colloidal and cellular level. Fluidic force microscopy, also called FluidFM, became a vital tool for biomedical applications. FluidFM combines AFM and nanofluidics by means of a microchanneled cantilever that bears an aperture instead of a tip at its end. Thereby, single colloids or cells can be aspirated and immobilized to the cantilever, for example, to determine adhesion forces. To allow for quantitative measurements, the so‐called (inverse) optical lever sensitivity (OLS and InvOLS, respectively) must be determined, which is typically done in a separate set of measurements on a hard, non‐deformable substrate. Here, we present a different approach that is entirely based on hydrodynamic principles and does make use of the internal microfluidic channel of a FluidFM‐cantilever and an external pressure control. Thereby, a contact‐free calibration of the (inverse) optical lever sensitivity (InvOLS) becomes possible in under a minute. A quantitative model based on the thrust equation, which is well‐known in avionics, and finite element simulations, is provided to describe the deflection of the cantilever as a function of the externally applied pressure. A comparison between the classical and the here‐presented hydrodynamic method demonstrates equal accuracy.